Diel-Regulated Transcriptional Cascades of Microbial Eukaryotes in the North Pacific Subtropical Gyre - Groussman, Ryan D.; Coesel, Sacha N.; Durham, Bryndan P.; Armbrust, E. Virginia (Frontiers in Microbiology, 2021)
Open-ocean surface waters host a diverse community of single-celled eukaryotic plankton (protists) consisting of phototrophs, heterotrophs, and mixotrophs. The productivity and biomass of these organisms oscillate over diel cycles, and yet the underlying transcriptional processes are known for few members of the community. Here, we examined a four-day diel time series of transcriptional abundance profiles for the protist community (0.2-100 μm in cell size) in the North Pacific Subtropical Gyre near Station ALOHA. De novo assembly of poly-A+ selected metatranscriptomes yielded over 30 million contigs with taxonomic and functional annotations assigned to 54% and 25% of translated contigs, respectively. The completeness of the resulting environmental eukaryotic taxonomic bins was assessed, and 48 genera were further evaluated for diel patterns in transcript abundances. These environmental transcriptome bins maintained reproducible temporal partitioning of total gene family abundances, with haptophyte and ochrophyte genera generally showing the greatest diel partitioning of their transcriptomes. The haptophyte Phaeocystis demonstrated the highest proportion of transcript diel periodicity, while most other protists had intermediate levels of periodicity regardless of their trophic status. Dinoflagellates, except for the parasitoid genus Amoebophrya, exhibit the fewest diel oscillations of transcript abundances. Diel-regulated gene families were enriched in key metabolic pathways; photosynthesis, carbon fixation, and fatty acid biosynthesis gene families had peak times concentrated around dawn, while gene families involved in protein turnover (proteasome and protein processing) are most active during the high intensity daylight hours. TCA cycle, oxidative phosphorylation and fatty acid degradation predominantly peaked near dusk. We identified temporal pathway enrichments unique to certain taxa, including assimilatory sulfate reduction at dawn in dictyophytes and signaling pathways at early evening in haptophytes, pointing to possible taxon-specific channels of carbon and nutrients through the microbial community. These results illustrate the synchrony of transcriptional regulation to the diel cycle, and how the protist community of the North Pacific Subtropical Gyre structure their transcriptomes to guide the daily flux of matter and energy through the gyre ecosystem.